Enhanced corrosion resistance of Ti65 alloys through chromium magnetron sputtering and laser remelting: A synergistic surface engineering strategy - Xinguo Chen; Wanming Li; Naixu Wang; Meng Qi; Yujing Liu; Zibo Zhao (Journal of Materials Research and Technology)
Near-α titanium alloy exhibits significant application potential in aerospace and chemical industries due to its exceptional mechanical strength and corrosion resistance. However, its performance degradation under chloride-rich environments (e.g., marine applications) necessitates surface engineering interventions. The Ti65 alloy, despite its outstanding mechanical properties, requires further surface optimization to enhance its corrosion resistance. This study develops a hybrid surface modification strategy that combines Cr magnetron sputtering with laser remelting to enhance the alloy's corrosion resistance. Systematic electrochemical testing in 3.5 wt% NaCl solution demonstrates a dual-protection mechanism: Cr solid-solution strengthening within the substrate matrix significantly improves corrosion resistance through enhanced passivation stability; the subsequent laser-remelted coating establishes a metallurgically bonded barrier layer, reducing corrosion current density from 5.0 × 10−7 A/cm2 (Ti65 substrates) to 1.2 × 10−7 A/cm2. This multiscale surface engineering approach offers a viable solution for deploying Ti65 alloys in marine and offshore applications where chloride-induced degradation prevails.